Evidence of a large cooling between 1690 and 1740 AD in southern Africa - Sundqvist, Hanna; Holmgren, K.; Fohlmeister, Jens; Zhang, Q.; Matthews, M. Bar; Spötl, C.; Körnich, H. (Scientific reports, 2013)
A 350-year-long, well-dated δ18O stalagmite record from the summer rainfall region in South Africa is positively correlated with regional air surface temperatures at interannual time scales. The coldest period documented in this record occurred between 1690 and 1740, slightly lagging the Maunder Minimum (1645-1710). A temperature reconstruction, based on the correlation between regional surface temperatures and the stalagmite δ18O variations, indicates that parts of this period could have been as much as 1.4°C colder than today. Significant cycles of 22, 11 and 4.8 years demonstrate that the solar magnetic and the El Niño-Southern Oscillation cycle could be important drivers of multidecadal to interannual climate variability in this region. The observation that the most important driver of stalagmite δ18O on interannual time scales from this subtropical region is regional surface temperature cautions against deterministic interpretations of δ18O variations in low-latitude stalagmites as mainly driven by the amount of precipitation.